Less IS less: a randomised controlled trial comparing cautious and rapid nalbuphine dosing regimens. Issue 3 (22nd April 2004) - Woollard, M; Whitfield, R; Smith, K; Jones, T; Thomas, G; Thomas, G; Hinton, C
Abstract : Objective: This study aimed to determine which of two paramedic administered nalbuphine dosing regimens combined the greater analgesic effect with the minimum of adverse events. Methods: Patients suffering from chest pain or trauma were randomised to receive either a rapid dosing regimen (10 mg over 30 seconds, repeated once after three minutes if pain score remained above three) or a cautious regimen (5 mg over two minutes, repeated at three minute intervals if pain score remained above three to a maximum dose of 20 mg). Data were collected on analgesic effectiveness, changes in vital signs, and patient reported side effects. Results: The pain score fell by a mean of 4.29 and 3.49 in the rapid and cautious regimen groups respectively (difference = 0.79, 95% CI 0.09 to 1.5, p = 0.028). However, over half the patients in both groups continued to suffer significant pain on arrival at hospital. There were no significant changes in vital signs after nalbuphine, but there was a greater incidence of patient reported drowsiness in rapid regimen patients (42% compared with 21%, 95% CI = 6.96 to 34.12%, p = 0.003). Conclusion: A rapid dosing regimen of nalbuphine using 10 mg increments is more effective than and equally as safe as a cautious regimen using 5 mg increments. Further research is required to determine if a maximum dose exceeding 20 mg would result in fewer patients continuing to suffer significant pain before arrival at hospital.